A review on microplastic ingestion in marine invertebrates from Southeast Asia - Haryati, Hasbudin; Mohd Nasarudin, Harith; Farah Akmal, Idrus (Prince of Songkla University, 2022)
The microplastic ingestion of marine invertebrates around ASEAN countries namely, Indonesia, Malaysia, Philippines, Thailand, and Vietnam were reviewed. The review involves locations, species, concentration of microplastics, as well as dominant colors and types of microplastics. The most studied species was Perna viridis. The highest concentration of microplastic was found in Laevistrombus turturella with 628 ±191.93 particles/individual. Black was the most common dominant color of microplastics and fiber was the most common type of microplastics found in the marine invertebrates. Two lab-based studies of microplastic ingestion in Acropora formosa and Perna viridis had shown detrimental effects of microplastics. The challenges of microplastic ingestion study around ASEAN was the possibility of microplastic entering seafood food security in both wild and farmed populations, as well as the probable collapse of the coral reef ecosystem.